ANALYSIS OF PUMP CAPACITY AT THE KARTINI V PUMP HOUSE IN CENTRAL JAKARTA - Imamuddin, Mohammad; Mahdiani, Nila Sekar (University Muhammadiyah Jakarta, 2024)
Kartini Volume Pump House is located at Jalan Kartini Raya Simpang Jalan Kartini V, RT. 01 RW. 04, Kartini Village, Sawah Besar District, Central Jakarta, Special Capital Region Of Jakarta, 10750. The geographical location of the pump is located at 6°09'14.4